PENGEMBANGAN UMKM KULINER SIOMAY DI DESTINASI WISATA TAMAN LASOSO UNTUK MENINGKATKAN EKONOMI LOKAL - Fidya Fidya; Amelia Amelia; Adinda Podung; I Kade Sindya Sanjaya; Dandan Haryono; Suasa Suasa; Nurhayati Hamid (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Lasoso Park has become a new icon in West Palu, where people can enjoy a public space to relax and socialize, with additional features such as a light tower and views of the Gawalise Mountains. Lasoso Park also rents various toy services and many culinary snacks, one of which is siomay. Siomay throughout its development is very popular among the Indonesian people and is easily found in snack places or existing parties. The method used is qualitative research, namely research that does not use mathematical, statistical, or computer models. Opportunities for MSME development in the Lasoso Park location offer various siomay variants such as fillings (eggs, meat, tofu, fried foods) and sauce variants, namely peanut sauce and firecrackers. The development strategy used in this siomay business is a digital marketing strategy and design promotion.